2017
DOI: 10.1016/j.ctro.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pulmonary 18 F-FDG-PET uptake and cytokine profiles in non-small cell lung cancer patients treated with radiotherapy and erlotinib

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to investigate the role of erlotinib in mitochondrial stress. Although erlotinib has been tested in several human clinical studies [ 57 , 58 ], its pharmacological mechanism has not been adequately explored. Our study proposed that the anti-cancer property of erlotinib relied on the activation of mitochondrial fragmentation by upregulating mitochondrial fission and downregulating mitochondrial fusion.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to investigate the role of erlotinib in mitochondrial stress. Although erlotinib has been tested in several human clinical studies [ 57 , 58 ], its pharmacological mechanism has not been adequately explored. Our study proposed that the anti-cancer property of erlotinib relied on the activation of mitochondrial fragmentation by upregulating mitochondrial fission and downregulating mitochondrial fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that lung 18 F-FDG uptake assessed typically six weeks after end of RT is associated with local radiation dose in the lung [15,16]. However, as pointed out in our previous study [20], this association may be false-positive due to other factors (anatomical/biological) showing high spatial correlation with radiation dose. Thus, difference map where the pre-therapy image series are implicitly taken as a control is most likely a better option.…”
Section: Discussionmentioning
confidence: 51%
“…However, the variations of the difference maps among patients were substantial, indicating significant variations in the lung response for individual patients. Also, we included patients randomized to either RT or RT plus concomitant erlotinib, and have previously found a difference in the lung 18 F-FDG uptake between these two study arms post-therapy [20]. This difference was still observed in the current analysis (only including patients with post-therapy 18 F-FDG-PET scan in addition to pre-therapy scan) both in DS and Dl (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…Various RT dose parameters such as V 10 (percentage of VOI receiving 10 Gy or more), V 15 , V 20 , and mean dose to the VOIs were calculated. RT data extraction have been done in IDL (Interactive Data Language, v 8.6, Research Systems, Boulder, CO, USA) as described previously [21].…”
Section: Rt Dose Parametersmentioning
confidence: 99%